2021
DOI: 10.3390/f12040422
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Association Analysis among Germplasms of Diospyros kaki in Zhejiang Province Based on SSR Markers

Abstract: In subtropical to temperate regions, persimmon (Diospyros kaki Thunb.) is an economically important fruit crop cultivated for its edible fruits. Persimmons are distributed abundantly and widely in Zhejiang Province, representing a valuable resource for the breeding of new cultivars and studying the origin and evolution of persimmon. In this study, we elucidated the genetic structures and diversity patterns of 179 persimmon germplasms from 16 different ecologic populations in Zhejiang Province based on the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Simple sequence repeats (SSRs, or microsatellites) are DNA stretches consisting of short, tandem units of sequence repetitions 1-6 base pairs in length [72]. We identified 87 SSRs in the D. oleifera mt genome.…”
Section: Repeat Sequences Analysismentioning
confidence: 99%
“…Simple sequence repeats (SSRs, or microsatellites) are DNA stretches consisting of short, tandem units of sequence repetitions 1-6 base pairs in length [72]. We identified 87 SSRs in the D. oleifera mt genome.…”
Section: Repeat Sequences Analysismentioning
confidence: 99%
“…Repeat sequences analysis. SSRs, or microsatellites, are DNA stretches consisting of short, tandem units of sequence repetitions of 1-6 base pairs in length 36 . In the current study, we identified 59 SSRs in the P. serratifolia mitogenome.…”
mentioning
confidence: 99%
“…Repeat sequences widely exist in plant mitogenomes, including tandem repeats and SSRs [ 61 ]. Positive correlations between genome size and repeat sequences were identified in 38 Rosaceae mitogenomes [ 62 ].…”
Section: Discussionmentioning
confidence: 99%